2006
DOI: 10.1038/ni1330
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid organ development: from ontogeny to neogenesis

Abstract: The development of lymphoid organs can be viewed as a continuum. At one end are the 'canonical' secondary lymphoid organs, including lymph nodes and spleen; at the other end are 'ectopic' or tertiary lymphoid organs, which are cellular accumulations arising during chronic inflammation by the process of lymphoid neogenesis. Secondary lymphoid organs are genetically 'preprogrammed' and 'prepatterned' during ontogeny, whereas tertiary lymphoid organs arise under environmental influences and are not restricted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
659
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(679 citation statements)
references
References 150 publications
13
659
1
6
Order By: Relevance
“…HEVs are specialized blood vessels, which, under nonpathological conditions, are found only in secondary lymphoid organs where they allow naïve T‐cell entry (reviewed in Ref. 13). As we have reported previously, however, HEVs are not found in unmanipulated MCA‐induced fibrosarcomas and thus cannot account for the enrichment of naïve T cells in these tumors 14…”
Section: Resultsmentioning
confidence: 99%
“…HEVs are specialized blood vessels, which, under nonpathological conditions, are found only in secondary lymphoid organs where they allow naïve T‐cell entry (reviewed in Ref. 13). As we have reported previously, however, HEVs are not found in unmanipulated MCA‐induced fibrosarcomas and thus cannot account for the enrichment of naïve T cells in these tumors 14…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, lymphoid organs share a cellular organization that includes a germinal centre comprising antibody secreting and proliferating B cells together with follicular dendritic cells (DCs); a T‐cell zone including naive cells recruited from the blood; high endothelial venules (HEV) for lymphocyte extravasation; and a network of stromal cells that provide chemokines and extracellular matrix for cellular migration and structural integrity 1, 3…”
Section: Secondary and Ectopic Lymphoid Organsmentioning
confidence: 99%
“…Likewise, as some tissues and tumours are more permissive to ELF development than others, the tissue microenvironment must contribute defined signals that are conducive to lymphoid neogenesis. In this regard, the development of ELFs mimics many of the mechanisms underpinning the organogenesis of SLOs (for a comprehensive review of SLO development see refs 1, 12). Here, initiation of SLO development centres on an interaction at the lymph node anlagen between haematopoietic derived CD4 + CD45 + CD3 − LTi cells and lymphoid tissue organizer (LTo) cells of mesenchymal origin.…”
Section: Cellular Initiators Of Ectopic Lymphoneogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The role of LT in the context of lymphoid neogenesis, development of autoimmune diseases and inflammatory disorders was further investigated in vivo (Picarella et al, 1992;Kratz et al, 1996;Luther et al, 2000;Drayton et al, 2003Drayton et al, , 2006Gommerman and Browning, 2003;Martin et al, 2004;Heikenwalder et al, 2005Heikenwalder et al, , 2008Haybaeck et al, 2009). These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues.…”
Section: Lt and Inflammationmentioning
confidence: 99%